Characterization of the treatment-naive immune microenvironment in melanoma with BRAF mutation. Issue 4 (5th April 2022) - Wang, Minyu; Zadeh, Soroor; Pizzolla, Angela; Thia, Kevin; Gyorki, David E; McArthur, Grant A; Scolyer, Richard A; Long, Georgina; Wilmott, James S; Andrews, Miles C; Au-Yeung, George; Weppler, Ali; et al.
Abstract : Background: Patients with BRAF -mutant and wild-type melanoma have different response rates to immune checkpoint blockade therapy. However, the reasons for this remain unknown. To address this issue, we investigated the precise immune composition resulting from BRAF mutation in treatment-naive melanoma to determine whether this may be a driver for different response to immunotherapy. Methods: In this study, we characterized the treatment-naive immune context in patients with BRAF -mutant and BRAF wild-type ( BRAF -wt) melanoma using data from single-cell RNA sequencing, bulk RNA sequencing, flow cytometry and immunohistochemistry (IHC). Results: In single-cell data, BRAF -mutant melanoma displayed a significantly reduced infiltration of CD8 + T cells and macrophages but also increased B cells, natural killer (NK) cells and NKT cells. We then validated this finding using bulk RNA-seq data from the skin cutaneous melanoma cohort in The Cancer Genome Atlas and deconvoluted the data using seven different algorithms. Interestingly, BRAF -mutant tumors had more CD4 + T cells than BRAF -wt samples in both primary and metastatic cohorts. In the metastatic cohort, BRAF -mutant melanoma demonstrated more B cells but less CD8 + T cell infiltration when compared with BRAF -wt samples. In addition, we further investigated the immune cell infiltrate using flow cytometry and multiplex IHC techniques. We confirmed that BRAF -mutant melanoma metastases were enriched for CD4 + T cells and B cells and had a co-existing decrease in CD8 + T cells. Furthermore, we then identified B cells were associated with a trend for improved survival (p=0.078) in the BRAF -mutant samples and Th2 cells were associated with prolonged survival in the BRAF -wt samples. Conclusions: In conclusion, treatment-naive BRAF -mutant melanoma has a distinct immune context compared with BRAF -wt melanoma, with significantly decreased CD8 + T cells and increased B cells and CD4 + T cells in the tumor microenvironment. These findings indicate that further mechanistic studies are warranted to reveal how this difference in immune context leads to improved outcome to combination immune checkpoint blockade in BRAF -mutant melanoma.